Book Notes [36, Fall 1995] - Palmer, Bryan D. (Labour/Le Travail, 1995)
The article briefly reviews "Law, Society, and the State: Essays in Modem Legal History," edited by Louis A. Knafla and Susan W.S. Binnie, "Public Sector Bargaining in Canada: Beginning of the End or End of the Beginning!," edited by Gene Swimmer and Mark Thompson, "Ships and Memories: Merchant Seafarers in Canada's Age of Steam ," by Eric Sager, "Canadian Women's Issues," 2 volumes. Volume I — "Strong Voices," by Roach Pierson, Marjorie Griffin Cohen, Paula Bourne, and Philinda Masters; Volume II — "Bold Visions," by Ruth Roach Pierson and Marjorie Griffin Cohen, "Strategies for the Year 2000: A Woman's Handbook," by Deborah Stienstra and Barbara Roberts, and Jean Barman, "Children, Teachers and Schools in the History of British Columbia," edited by Neil Sutherland and J. Donald Wilson, "Four Quarters of the Night: The Life Journey of an Emigrant Sikh," by Tara Singh Bains and Hugh Johnston, "Under the Northern Lights: My Memories of Life in the Finnish Community of Northern Ontario," by Edward W. Laine, edited by Nelma Sillanpaa, "Sojourners and Settlers: The Macedonian Community in Toronto to 1940," by Lillian Petroff, "The Dynamics of Industrial Competition: A North American Perspective," by John R. Baldwin, "Regional Integration and Industrial Relations in North America," edited by Maria Lorena Cook and Harry C. Katz, "From Chattel Slaves to Wage Slaves: The Dynamics of Labour Bargaining in the Americas," edited by Mary Turner, "Conflicting Paths: Growing Up in America," by Harvey J. Graff, "Industrializing America: The Nineteenth Century," by Walter Licht, "Anarchist Voices: An Oral History of Anarchism in America," by Paul Avrich, "The Populist Persuasion: An American History," by Michael Kazin, "American Labor in the Era of World War II," edited by Sally M. Miller and Daniel A. Cornford, "Aspects of Political Censorship, 1914-1918," by Tania Rose, "The Imagined Slum: Newspaper Representation in Three Cities, 1870-1914," by Alan Mayne, "Gender and the Politics of Social Reform in France, 1870-1914," edited by Elinor A. Accampo, Rachel G. Fuchs, and Mary Lynn Stewart, "A New International History of the Spanish Civil War," by Michael Alpert, "The Wartime System of Labor Service in Hungary: Varieties of Experience," edited by Randolph L. Braham, "Trade Union Growth and Decline: An International Study," by Walter Galenson, "Workplace Industrial Relations and the Global Challenge," edited by Jacques Bélanger, P.K. Edwards, and Larry Haiven, "Industrialization and Labor Relations: Contemporary Research in Seven Countries," edited by Stephen Frenkel and Jeffrey Harood, "Contemporary Collective Bargaining in the Private Sector," edited by Paula B. Voos, "Women in the Latin American Development Process," edited by Christine E. Bose and Edna Acosta Belen, and "Imagining Home: Class, Culture and Nationalism in the African Diaspora," by Sidney Lemelle and Robin D.G. Kelley,